Work Stress Management Nurse RSUD dr. M.M Dunda Limboto - Abd. Kadim Masaong; Sabirin B. Syukur; Mohamad Ariyanto Tuna (PROMOTOR, 2024)
Job or work-related stress is a response that a person may have when faced with demands and work pressures that are not their knowledge and ability to be able to handle it. The purpose of this study is to find out how the stress management of nurses at RSUD dr. M.M Dunda Limboto. This research method is quantitative research with a descriptive analysis research design. Data collection was carried out using questionnaire sheets with a population of 73 respondents. The number of respondents was taken using purposive sampling techniques. The data was obtained by statistically using frequency distribution. The results of nurses' work stress management with an individual approach with sufficient category 60.3%, organizational approach sufficient category 57.5%, and social approach sufficient category 50.7%. It is suggested that this study is expected to add references to health services on how stress management in nurses.